BIRTH AS A SOURCE OF IDEAS FOR THE CREATION OF TEXTILE ARTWORK - Shofia Ajiba Al-Haqiqi (ARTISTIC : International Journal of Creation and Innovation, 2020)
The design is intended to create new work that focus on textile artwork to convey messages related to birth by exploring visual, symbol, and processing colors and techniques. The purpose of this artwork is to convey messages related to anti-drug awareness through textile artwork for an aesthetic element of the interior. The method used in this creation is the Gustami approach. This method goes through 6 stages, namely finding references in order to explore themes and topics, searching for theoretical foundations to determine techniques, materials, problems in creation, sketching, sketch completion, embodiment, and evaluation. The results of this design showed that (1) exploration in creating interior aesthetic artwork with the source of the idea of "birth" can be done by searching for layered data which is then outlined in a sketch taking into account colors and symbols, and (2) the work is realized with embroidery can be used to convey messages to raise anti-drug awareness in young generations.